Inclusive educational environment for children with autism in malaysian primary schools - Rahaman, Farjana; Abdul Rahim, Asiah; Abdullah, Fadzidah (IIUM Press, International Islamic University Malaysia, 2017)
Inclusion of children with autism in the mainstream school falls under a regulation in Malaysia. However, existing school buildings still lack in providing enabling environment for children with autism. Moreover, current building standards and policies fail to address the wayfinding design requirements of these children in mainstream educational settings. The present research implies that wayfinding performance of children with autism can be improved by providing an appropriate environment design. This research employs both qualitative and quantitative research methods based on environment and behavior studies. Objectives of this study are (1) to identify different architectural elements that impact on the wayfinding of children with autism and ablebodied children, (2) to investigate the existing condition of the primary school buildings in Malaysia in terms of inclusive wayfinding design and finally (3) to suggest a model as a set of tools for design practice that would ensure an appropriate and inclusive learning environment for children with autism, in the context of Malaysia.